Over-accumulation, Rising Costs and 'Unproductive' Labor: The Relevance of the Classic Stationary State Issue for Developed Countries. (March 2014) - Durand, Cédric; Légé, Philippe
The current crisis takes place within a long downturn and new debates on the future of growth are emerging. This paper argues that some theoretical insights made by classical economists about the end of economic expansion are relevant for the discussion on the prospects for growth in rich countries. We focus on three key mechanisms related to contemporary radical economic analysis: over-accumulation, rising costs of accumulation, and the balance between productive and unproductive labor and consumption.